Care and Feeding of Metropolitan Dailies and Wire Services - Joseph J. Marks (Journal of Applied Communications, 1984)
Due in part to Ovid Bay's remarks at last year's ACE Conference (see Oct-Dec 1983 ACE Quarterly), I have felt for some time that improvements in technology are confusing the basic issues of how we become credible sources of useful information to gatekeepers and their audiences - and stay that way.